Rehabilitation after Clipping of Cerebral Aneurysms without Acute Subarachnoid Hemorrhage: Outcome Analysis of 100 Consecutive Cases - Jödicke, Andreas; Bauer, Karsten; Hajdukova, Andrea (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Discharge to rehabilitation is reported in large studies as one important outcome parameter based on hospital codes. Because neurologic outcome scores (e.g., the modified Rankin Scale [mRS]) are missing in International Classification of Diseases (ICD) databases, rehabilitation indirectly serves as a kind of surrogate parameter for overall outcome. Reported fractions of patients with rehabilitation, however, largely differ between studies and seem high for patients with aneurysm clipping. Variances in rehabilitation fractions seem to largely differ between treatments (clipping versus coiling) for unruptured intracranial aneurysms, so we analyzed our patients for percentage of and potential factors predicting rehabilitation.Patients From July 2007 to September 2013, 100 consecutive patients with at least one cerebral aneurysm underwent aneurysm clipping. Aneurysms were classified as incidental, associated, pretreated (coil compaction after subarachnoid hemorrhage), and symptomatic (oculomotor nerve compression, microemboli), and they were assigned to their anatomical location. Complications (infection, hemorrhage, cerebrospinal fluid fistula, transient and permanent neurologic deficit, reoperation) and outcome (mRS at 6 months; clip occlusion rate by postoperative digital subtraction angiography) as well as frequency and type of rehabilitation were analyzed and correlated retrospectively. Multiple aneurysms clipped in one procedure were not counted separately regarding complications or outcome (i.e., one patient, one outcome).Results The overall complication rate was 17% including 10% early and 3% permanent neurologic deficits and 7% reoperations. There were no deaths. Overall, 98% of patients had a good outcome (mRS 0–2). Clip occlusion rate was 97.9%. Multivariate logistic regression analysis identified aneurysm location as the only significant independent factor for risk of complication (p < 0.001) and complication as the only significant independent risk factor for rehabilitation (p = 0.003). Rehabilitation was indicated or requested by the patient as early neurologic rehabilitation (5%), inpatient follow-up (15%), and outpatient follow-up (15%). The long-term care rate was 2%.Conclusion Microsurgery of unruptured and not acutely ruptured aneurysms (including post-coil and associated aneurysms) has a low rate of rehabilitation with a low risk of a permanent neurologic deficit, long-term care, or early neurologic rehabilitation. The rate of rehabilitation is well below reported risks from studies based on ICD-based health care analysis. Rehabilitation per se is not a good indicator for outcome.
Keywords: aneurysm; cerebral; rehabilitation; long-term care